Orbital hopping maneuvers with two Astrobee free-flyers: Ground and flight experiments - Kwok-Choon, Stephen; Hudson, Jennifer; Romano, Marcello (Frontiers in Robotics and AI, 2022)
Dynamic hopping maneuvers using mechanical actuation are proposed as a method of locomotion for free-flyer vehicles near or on large space structures. Such maneuvers are of interest for applications related to proximity maneuvers, observation, cargo carrying, fabrication, and sensor data collection. This study describes a set of dynamic hopping maneuver experiments performed using two Astrobees. Both vehicles were made to initially grasp onto a common free-floating handrail. From this initial condition, the active Astrobee launched itself using mechanical actuation of its robotic arm manipulator. The results are presented from the ground and flight experimental sessions completed at the Spacecraft Robotics Laboratory of the Naval Postgraduate School, the Intelligent Robotics Group facility at NASA Ames Research Center, and hopping maneuvers aboard the International Space Station. Overall, this study demonstrates that locomotion through mechanical actuation could successfully launch a free-flyer vehicle in an initial desired trajectory from another object of similar size and mass.